Subacute Toxicity Profile of Lacidipine Nanoformulation in Wistar Rats. (25th May 2015) - Shirodkar, Rupesh; Misra, Chandrasekhar; GH, Chethan; Shetty, Pallavi; Attari, Zenab; Mutalik, Srinivas; Lewis, Shaila
Abstract : The present study was aimed at investigating the safety of Lacidipine (LCDP) loaded nanostructured lipid carriers (NLCs) in Wistar rats. NLCs were formulated using ultrasound dispersion technique. Animals were orally treated once daily with NLCs containing 0.140 mg, 0.350 mg, and 0.875 mg of LCDP as low, medium, and high dose per kg body weight, respectively, during 28 days along with blank formulation and pure LCDP. Control rats were fed with water. Animals were observed throughout experiment period and their body weight was recorded once weekly. Overnight fasted rats were sacrificed on the 29th day. Study revealed no signs or symptoms of toxicity or morbidity. No significant changes in the body weight were observed between treated and control group. Significant increase in left testis weight and liver weight was observed in male and female rats, respectively. Haematological estimation revealed significant decrease in haemoglobin count in male rats while female rats showed significant increase in granulocyte count. All the serum clinical parameters were within the normal range and no gross histopathological changes were observed. No delayed effect was noted in satellite group. The results indicate that developed LCDP loaded NLCs are safe when administered orally in rats.